Study of anti-diabetic, beta-carotene-bleaching inhibiting and iron chelating properties of Carissa opaca root extracts (Brazilian Journal of Pharmaceutical Sciences, 2022)
Degenerative diseases diabetes and oxidative stress constitute a major health concern worldwide. Medicinal plants are expected to provide effective and affordable remedies. The present research explored antidiabetic and antioxidant potential of extracts of Carissa opaca roots. Methanolic extract (ME) was prepared through maceration. Its fractions were obtained, sequentially, in hexane, chloroform, ethyl acetate and n-butanol. An aqueous decoction (AD) of the finely ground roots was obtained by boiling in distilled water. The leftover biomass with methanol was boiled in water to obtain biomass aqueous decoction (BAD). The extracts and fractions showed considerable porcine pancreatic α-amylase inhibitory activity with IC50 in the range of 5.38-7.12 mg/mL while acarbose had 0.31 mg/mL. The iron chelating activity in terms of EC50 was 0.2939, 0.3429, 0.1876, and 0.1099 mg/mL for AD, BAD, ME, and EDTA, respectively. The EC50 of beta-carotene bleaching activity for AD, BAD, ME, and standard BHA were 4.10, 4.71, 3.48, and 2.79 mg/mL, respectively. The total phenolic content (TPC) and total flavonoid content (TFC) of AD and BAD were also considerable. In general, ethyl acetate fraction proved to be the most potent. Thus, the C. opaca roots had excellent antioxidant activity while having moderate α-amylase inhibitory potential.